Illustrated C# 2005 - Solis, Daniel (Apress, 2012)
The purpose of this book is to teach you the fundamentals and mechanics of the C# programming language. Most books teach programming primarily using text. That’s great for novels, but many of the important concepts of programming languages can best be understood through a combination of words, figures, and tables. Many of us think visually, and figures and tables can help clarify and crystallize our understanding of a concept. In several years of teaching programming languages, I have found that the pictures I drew on the whiteboards were the things that most quickly helped the students understand the concepts I was trying to convey. Illustrations alone, however, are not sufficient to explain a programming language and platform. The goal of this book is to find the best combination of words and illustrations to give you a thorough understanding of the language, and to allow the book to serve as a reference resource as well. This book is written for anyone who wants an introduction to the C# programming language—from the novice to the seasoned programmer. For those just getting started in programming, I have included the basics. For seasoned programmers, the content is laid out succinctly, and in a form that will allow you to go directly to the information required without having to wade through oceans of words. For both sets of programmers, the content itself is presented graphically, in a form that should make the language easy to learn.